PENINGKATAN KAPASITAS KADER MELALUI PELATIHAN MANAJEMEN POSBINDU INTEGRASI LAYANAN PRIMER DI RW XI P4A KELURAHAN PUDAKPAYUNG KOTA SEMARANG - Priyanto; Untari; Ummu Muntamah; Ade Pratama; Mufidatun Qothrun Nada; Salma Nadia; Afni Nadya Ramdhani (Universitas 'Aisyiyah Surakarta, 2025)
Chronic diseases are a major health problem in Indonesia, including in Semarang City, with risk factors affecting 37% of the adult population in RW XI P4A, Pudakpayung Village. However, the capacity of Posbindu ILP cadres for the prevention and management of chronic diseases is still low. This community service program aims to improve the capacity of cadres through Posbindu ILP management training. The method used was descriptive quantitative with a pre-post intervention approach applied to 20 cadres. The intervention included theoretical material on administration, service flow, early detection of chronic disease risk factors, counselling, and referral, as well as simulated practice of service flow, manual and digital recording, and role-play counselling and referral. Data were collected through questionnaires and practice observation and analysed using the Wilcoxon Signed Rank Test. The results showed significant improvements in all aspects: understanding of governance (p=0.003), recording and reporting (p=0.001), early detection of chronic disease risks (p=0.006), counselling and health education (p=0.008), and referral and follow-up of participants (p=0.010). Self-confidence (95%) and teamwork (100%) also increased. This training has proven effective in improving the capacity of cadres. It is recommended that mentoring and further training be provided on a regular basis, that record-keeping and administration be standardised, and that community participation continue to be increased in order to maintain the sustainability of ILP Posbindu services